Trichoderma – genomes and genomics as treasure troves for research towards biology, biotechnology and agriculture - Schalamun, Miriam; Schmoll, Monika (Frontiers in Fungal Biology, 2022)
The genus Trichoderma is among the best studied groups of filamentous fungi, largely because of its high relevance in applications from agriculture to enzyme biosynthesis to biofuel production. However, the physiological competences of these fungi, that led to these beneficial applications are intriguing also from a scientific and ecological point of view. This review therefore summarizes recent developments in studies of fungal genomes, updates on previously started genome annotation efforts and novel discoveries as well as efforts towards bioprospecting for enzymes and bioactive compounds such as cellulases, enzymes degrading xenobiotics and metabolites with potential pharmaceutical value. Thereby insights are provided into genomes, mitochondrial genomes and genomes of mycoviruses of Trichoderma strains relevant for enzyme production, biocontrol and mycoremediation. In several cases, production of bioactive compounds could be associated with responsible genes or clusters and bioremediation capabilities could be supported or predicted using genome information. Insights into evolution of the genus Trichoderma revealed large scale horizontal gene transfer, predominantly of CAZyme genes, but also secondary metabolite clusters. Investigation of sexual development showed that Trichoderma species are competent of repeat induced point mutation (RIP) and in some cases, segmental aneuploidy was observed. Some random mutants finally gave away their crucial mutations like T. reesei QM9978 and QM9136 and the fertility defect of QM6a was traced back to its gene defect. The Trichoderma core genome was narrowed down to 7000 genes and gene clustering was investigated in the genomes of multiple species. Finally, recent developments in application of CRISPR/Cas9 in Trichoderma, cloning and expression strategies for the workhorse T. reesei as well as the use genome mining tools for bioprospecting Trichoderma are highlighted. The intriguing new findings on evolution, genomics and physiology highlight emerging trends and illustrate worthwhile perspectives in diverse fields of research with Trichoderma. .